Gut bacterial and fungal communities of the domesticated silkworm (Bombyx mori) and wild mulberry-feeding relatives - Chen, Bosheng; Du, Kaiqian; Sun, Chao; Vimalanathan, Arunprasanna; Liang, Xili; Li, Yong; Wang, Baohong; Lu, Xingmeng; Li, Lanjuan; Shao, Yongqi (The ISME Journal, 2018)
Bombyx mori , the domesticated silkworm, is of great importance as a silk producer and as a powerful experimental model for the basic and applied research. Similar to other animals, abundant microorganisms live inside the silkworm gut; however, surprisingly, the microbiota of this model insect has not been well characterized to date. Here, we comprehensively characterized the gut microbiota of the domesticated silkworm and its wild relatives. Comparative analyses with the mulberry-feeding moths Acronicta major and Diaphania pyloalis revealed a highly diverse but distinctive silkworm gut microbiota despite thousands of years of domestication, and stage-specific signatures in both total (DNA-based) and active (RNA-based) bacterial populations, dominated by the phyla Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes. Most fungal sequences were assigned to the phyla Ascomycota and Basidiomycota. Environmental factors, including diet and human manipulation (egg production), likely influence the silkworm gut composition. Despite a lack of spatial variation along the gut, microbial community shifts were apparent between early instars and late instars, in concert with host developmental changes. Our results demonstrate that the gut microbiota of silkworms assembles into increasingly identical community throughout development, which differs greatly from those of other mulberry-feeding lepidopterans from the same niche, highlighting host-specific effects on microbial associations and the potential roles these communities play in host biology.